Review of Ice Slurry Storage in the Ice Storage Tank - Zhao Mei; Yu Hang (Zhileng xuebao, 2013)
Ice slurry storage in the storage tank often occurs in practical projects. The ice slurry storage characteristics have an important influence on the ice slurry application. The main problem of ice slurry storage is the nonuniformity and the low utilization of ice slurry storage tank. The research achievements about ice slurry storage reported in domestic and international literatures were collected and summarized from the aspects of characteristics, model and experimental study. It is found that image method is often used to analyze ice slurry storage characteristics and the main influence factors on the storage characteristics are solution, additives, ice slurry IPF (ice packing factor) and flow rate at the entrance and storage time. The analysis of the present situation of ice slurry storage provides references to the further research.